Factors that contribute to the difficult in solving Mathematical word problem base on Newman Error Analysis among Year 3 pupils in SK Seruyuk, Simunjan / Asman Hassan - Hassan, Asman (2016)
Objectives of this research are to find the factor that contribute to the difficulties in solving Mathematical word problems base on Newman Error Analysis among year 3 SK Seruyuk, Simunjan. This research will analyze cause and factor mistake which always done by pupil while solve problem story based on Newman Error Analysis. Research respondents are 10 students from year 3 at SK Seruyuk, Simunjan. Respondents will tested at classroom in written test form which consisting of 10 questions. The results also show that most respondents exactly have a problem mathematical word problem. A researcher find the problem faced by cause an error weather a causes from reading, comprehension, transformation, application process skill or ability to encoding. In addition, many respondents are facing mistakes in terms of carelessness, incorrect computation or calculation, misconception numeral method, wrong place value, not showing a calculation, and weak I basic fact involve addition, subtraction, multiplication and division. While based on questionnaires regarding respondents' views of mathematics subject, almost a respondent given positive feedback and as one of the preferred subjects. However they admit that mathematical word problem is very difficult to learn.